Analysis of Android Applications on Google Play Store as a Learning Media for Java Programming Language - Bara Bintang Pradana; Endar Suprih Wihidayat; Puspanda Hatta (Journal of Informatics and Vocational Education, 2025)
Despite the proliferation of Java programming learning applications on mobile platforms, no systematic quality-based framework has been applied to evaluate their instructional adequacy, leaving educators without reliable evidence for media selection. This study aims to systematically evaluate Java programming learning applications available on the Google Play Store to identify those most suitable for use as instructional media. A descriptive qualitative approach with structured assessment was employed, in which applications were systematically collected using predefined keywords and filtered through a six-stage elimination process prior to evaluation. The remaining 30 applications were assessed using the Learning Object Review Instrument (LORI), which evaluates seven aspects: content quality, learning objective alignment, feedback and adaptation, motivation, presentation design, interaction usability, and accessibility. Each aspect was scored on a scale of 1 to 4, and a final percentage score was calculated for each application. Of the 30 applications assessed, three achieved the highest scores: CodeGym (92), Java by Coding and Programming (90), and Java X (89), all of which demonstrated strong performance across content quality and usability dimensions. Notably, Google Play Store user ratings were found to be inversely proportional to LORI-based instructional quality scores, suggesting that popularity metrics do not reflect pedagogical value. These findings indicate that a structured, criteria-based evaluation framework is essential for educators selecting Java learning applications, and that Play Store ratings alone are insufficient as a proxy for instructional quality. Future studies are recommended to validate these findings through user testing with actual learners across multiple educational contexts.